2015
DOI: 10.1007/s00264-015-2890-8
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical analysis of acromioclavicular joint dislocation treated with clavicle hook plates in different lengths

Abstract: The findings of this study can serve as a reference to help orthopaedic surgeons select clavicle hook plates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
34
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 21 publications
0
34
0
Order By: Relevance
“…These simulations can effectively and efficiently evaluate a lot of variables such as surgical techniques and implant types used for various pathologies to optimize design, screening, prediction, and cost‐effectively in the treatment in orthopedics . Previously, several studies investigated the biomechanics of AC joint and human shoulder complex by using FEA …”
Section: Introductionmentioning
confidence: 99%
“…These simulations can effectively and efficiently evaluate a lot of variables such as surgical techniques and implant types used for various pathologies to optimize design, screening, prediction, and cost‐effectively in the treatment in orthopedics . Previously, several studies investigated the biomechanics of AC joint and human shoulder complex by using FEA …”
Section: Introductionmentioning
confidence: 99%
“…Works on computer-based simulation and investigation of bone osteosynthesis plates made of magnesium alloys are not abundant (Shirurkara, Tamboli, Jagtap, Dondapati, & Davidson, 2017). More frequently, bone fixations plates produced of the traditional materials (titanium alloys and stainless steel) are investigated (Lee et al, 2016;Shih, Huang, Pan, Lee, & Su, 2015;Hung, Su. Lu, & Lee, 2017;Cronskar, Rasmussen, & Tinnsten, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In other work (Shih et al, 2015), models of the clavicle, a fragment of the shoulder bone and the joint fixation plates were developed. A simplified model of a joint fixation plate was developed upon taking into account the models offered in the market in that period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, different implants and methods of internal fixation as well as the mechanical effects of clavicle fixation are also explored . In addition, some scholars also indicated that using a longer clavicle hook plate decreased and mitigated the force that clavicle hook plates exert on the acromion and the stress value in the clavicle .…”
mentioning
confidence: 99%